2015
DOI: 10.1111/1440-1681.12470
|View full text |Cite
|
Sign up to set email alerts
|

CCN2 and CCN5 exerts opposing effect on fibroblast proliferation and transdifferentiation induced by TGFβ

Abstract: Epidural fibrosis might occur after lumbar discectomy and contributes to failed back syndrome. Transforming growth factor (TGF)-β has been reported to influence multiple organ fibrosis, in which connective tissue growth factor/cysteine-rich 61/nephroblastoma overexpressed 2 (CCN2) and CCN5 are involved. However, the effect of CCN2 and CCN5 on TGF-β induced fibrosis has not yet been elucidated. This study reports that CCN2 and CCN5 play opposing roles in cell proliferation and transdifferentiation of human skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…PDGFAA upregulated proliferation only in SSc fibroblasts (Figure 2a) and crenolanib blocked this response. We also examined the mitogenic effect of CCN2, which has previously been reported to indirectly induce fibroblast proliferation (Xu et al, 2015). Interestingly, while CCN2 alone had no effect, addition of PDGFAA together with CCN2 induced proliferation of HC fibroblasts with similar potency to that of PDGFBB (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…PDGFAA upregulated proliferation only in SSc fibroblasts (Figure 2a) and crenolanib blocked this response. We also examined the mitogenic effect of CCN2, which has previously been reported to indirectly induce fibroblast proliferation (Xu et al, 2015). Interestingly, while CCN2 alone had no effect, addition of PDGFAA together with CCN2 induced proliferation of HC fibroblasts with similar potency to that of PDGFBB (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…As explained in the introduction, CCNs (sometimes called matricellular proteins) are involved in cell‐to‐cell signaling and play important roles in ECM regulation . CCN5 is unique because it lacks a C‐terminal repeat domain and acts as a negative regulator of other CCNs, especially CCN2 . Several recent studies have established the anti‐fibrotic and anti‐hypertrophic effects of CCN5, and the majority of them have shown that CCN5 may modulate the TGF‐β pathway when acting on fibroblasts …”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast differentiation is an additional critical aetiology in the development of pulmonary fibrosis. Accompanying changes in the microenvironment include the overproduction of a key factor, TGF‐β1, resulting in the activation of fibroblasts into myofibroblasts and production of abundant levels of ECM in the interstitial tissues of the lungs, leading to irreversible damage to lung architecture and pulmonary fibrosis . Our results revealed that lanatoside C treatment was capable of reducing the expression of α‐SMA, fibronectin and collagens I and III in response to TGF‐β1, indicating a suppression role for lanatoside C during the differentiation process of fibroblasts into myofibroblasts.…”
Section: Discussionmentioning
confidence: 67%